'I care a lot' a commentary on the depiction of elder abuse in the film. Issue 4 (8th August 2021) - Beaulieu, Marie; St-Martin, Kevin; Cadieux Genesse, Julien
ABSTRACT: In I Care a Lot, we follow Marla Grayson, a self-proclaimed "Professional Carer" who makes a living by financially abusing older adults. Elder abuse, financial or otherwise, is seldom explored in cinema and must be handled with care. Cinema can help raise awareness on this social problem and play an important role in the de-stigmatization of older adults. Unfortunately, in our opinion, I Care a Lot fails to do so.